Compendium of Economic and Trade Indicators by Region, 1960 to 2004 - Sandri, Damiano (Washington, DC: World Bank, 2022)
This compilation of data is prepared as a companion to the Bank's research project on distortions to agricultural incentives. Its purpose is to provide comparative basic economic and trade indicators for the countries involved as case studies in that project. The project is global in coverage, and is sub-divided into five groups: Africa, Asia, Europe and Central Asia's Transition Economies, Latin America and the Caribbean, and high-income countries. The present compendium is divided into seven main sections. The first one includes data on high income countries which are compared with three aggregates for developing countries. Sections two through five focuses indeed specifically on one of the four regional groups and compare data for the case study countries with various aggregates of studied and not studied countries. Due to the very limited data availability several countries have not been included in the compendium. Finally, section six and seven include estimates of trade distortions, and sectoral shares of value added and household expenditures for all the studied countries and several regional aggregates.